On the application of the Theory of Critical Distances for prediction of fracture in fibre composites - David Taylor (Fracture and Structural Integrity)
This paper is concerned with the fracture of composite materials containing stress concentration features such as notches and holes. In particular, it addresses the question of the use of the Theory of Critical Distances (TCD) – a method which is widely used for predicting notch effects in fatigue and fracture. The TCD makes use of a length constant, L, known as the critical distance, which is normally assumed to be a material property. However, many workers in the field of composite materials have suggested that the critical distance is not a constant, but rather is a function of notch size. I examined the evidence for this assertion, and concluded that it arises for four different reasons, two of which (process zone size and constraint) are real material effects whilst the other two (choice of test specimen and estimation of the stress field) arise due to errors in making the assessments. From a practical point of view, the assumption of a constant value for L leads to only small errors, so it is recommended for engineering design purposes.